2012
DOI: 10.1016/j.neurobiolaging.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Hourly variability of cerebrospinal fluid biomarkers in Alzheimer's disease subjects and healthy older volunteers

Abstract: Large hour-to-hour variability has previously been demonstrated in the cerebrospinal fluid (CSF) concentrations of Alzheimer's disease (AD) biomarkers amyloid β(42) (Aβ(42)) and Aβ(40) in healthy younger subjects. We investigated the within-subject variability over 36 hours in CSF Aβ and tau proteins, in older subjects and AD patients. Six patients with mild stage AD (59-85 years, Mini Mental State Examination (MMSE) 16-26) and 6 healthy older volunteers (64-77 years) received an intrathecal catheter from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…For a detailed description of the methods, we refer to a previous publication. 5 Glucose was measured with the hexokinase method, using a Cobas Mira analyzer. 3 …”
Section: Methodsmentioning
confidence: 99%
“…For a detailed description of the methods, we refer to a previous publication. 5 Glucose was measured with the hexokinase method, using a Cobas Mira analyzer. 3 …”
Section: Methodsmentioning
confidence: 99%
“…As a result, biomarkers or drugs are expected to be concentrated in the smaller volume of fluid of the old or with certain diseases. For example, Slats et al [160] sampled 6 ml of patients' CSF every hour for 36 h using indwelling L3-4 lumber puncture cannula. They noted total CSF protein and pathological tau increased over the study period in the Alzheimer's disease patients, but not in age-matched controls, suggesting an artefact in sampling from the frailer patients.…”
Section: Practical and Clinical Implications Of Isf/csf Interactionmentioning
confidence: 99%
“…Most studies using enzyme-linked immunosorbent assays (ELISA) have not found any difference in CSF Aβ 42 and Tau levels after one freeze/thaw cycle [16,18,33,35,36], [Leitao submitted]. In contrast, one study found a significant loss of Aβ 42 after one single freeze/thaw cycle using a semi-quantitative method [37].…”
Section: Storage Conditionsmentioning
confidence: 99%
“…A diurnal variability was observed for Aβ peptides according to one study [40]. However, more recent studies were unable to replicate the finding that there is a temporal fluctuation in the CSF biomarker levels (Aβ, t-Tau and p-Tau) [16,41,42]. Therefore, there is no need to standardize a specific time interval during the day for CSF collection dedicated to AD biomarker assays.…”
Section: Other Factors With Minor or Without Effect: No Need Of Specimentioning
confidence: 99%